How to induce superconductivity in epitaxial graphene via remote proximity effect through an intercalated gold layer. (9th October 2020) - Mazaleyrat, Estelle; Vlaic, Sergio; Artaud, Alexandre; Magaud, Laurence; Vincent, Thomas; Cristina Gómez-Herrero, Ana; Lisi, Simone; Singh, Priyank; Bendiab, Nedjma; Guisset, Valérie; David, Philippe; Pons, Stéphane; et al.
Abstract: Graphene holds promises for exploring exotic superconductivity with Dirac-like fermions. Making graphene a superconductor at large scales is however a long-lasting challenge. A possible solution relies on epitaxially-grown graphene, using a superconducting substrate. Such substrates are scarce, and usually destroy the Dirac character of the electronic band structure. Using electron diffraction (reflection high-energy, and low-energy), scanning tunneling microscopy and spectroscopy, atomic force microscopy, angle-resolved photoemission spectroscopy, Raman spectroscopy, and density functional theory calculations, we introduce a strategy to induce superconductivity in epitaxial graphene via a remote proximity effect, from the rhenium substrate through an intercalated gold layer. Weak graphene–Au interaction, contrasting with the strong undesired graphene–Re interaction, is demonstrated by a reduced graphene corrugation, an increased distance between graphene and the underlying metal, a linear electronic dispersion and a characteristic vibrational signature, both latter features revealing also a slight p doping of graphene. We also reveal that the main shortcoming of the intercalation approach to proximity superconductivity is the creation of a high density of point defects in graphene (10 14 cm −2 ). Finally, we demonstrate remote proximity superconductivity in graphene/Au/Re(0001), at low temperature.